cos(x)+cos(2x)=-1

Simple and best practice solution for cos(x)+cos(2x)=-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for cos(x)+cos(2x)=-1 equation:


Simplifying
cos(x) + cos(2x) = -1

Multiply cos * x
cosx + cos(2x) = -1

Remove parenthesis around (2x)
cosx + cos * 2x = -1

Reorder the terms for easier multiplication:
cosx + 2cos * x = -1

Multiply cos * x
cosx + 2cosx = -1

Combine like terms: cosx + 2cosx = 3cosx
3cosx = -1

Solving
3cosx = -1

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Divide each side by '3osx'.
c = -0.3333333333o-1s-1x-1

Simplifying
c = -0.3333333333o-1s-1x-1

See similar equations:

| y^2+12y+36=r | | g(-3)=2x^3+2 | | -2x+10=3x+45 | | -2*25+2y=44 | | c/4=1`6 | | 0.03(y-7)+0.14y=0.07y-0.20 | | 9x(2x-4)= | | 3x-9y=-21 | | 13=1-13 | | 27x+14=3(9x-7) | | 2e-8=14# | | -5(6x-4)= | | 6f=-5x+2 | | Y-5x=-8 | | 2x^2+5=-32 | | (-35)x(-14)x(0.5)= | | -81-4(7-3x)=13(x-8) | | 84-48/8 | | .25t+9=3 | | 2x-10x=30 | | (4x-9)(10x+5)=0 | | f(x)=-5x^2+2x-1 | | x^2-4x/x | | 2*-10-9y=38 | | 46-1+8x=18x-15 | | 6n-3-9n=4+2n-8 | | 28-3c+4=2c+6+1c | | 18/5-2k=6 | | 11x-7=7+9a | | 4(2p-8)-6p=20-4(p+6) | | 28-3c+4=2c+6+c | | 2a+4=6a+8 |

Equations solver categories